Echocardiographic Parameters of Callithrix spp. Under Human Care - Melina Castilho de Souza Balbueno; Jessica Amancio Martins; Soraya Kezam Malaga; Ralph Eric Thijl Vanstreels; Cideli de Paula Coelho (Animals, 2025)
Non-human primates are frequently used in anatomical and physiological research due to their similarity to humans. Currently, echocardiographic reference values are missing. Therefore, this study evaluated echocardiographic parameters in Callithrix spp., focusing on marmoset species under human care. Using color Doppler, M-mode, and B-mode, in a MyLab Gamma device (Esaote, Italy), examinations were conducted on 168 clinical healthy animals of the species Callithrix penicillata, C. aurita, C. jacchus, and hybrids, of both sexes, with an average weight of 328 ± 71 g. The samples were collected from the Mucky Project and the São Bernardo do Campo Zoo in São Paulo, Brazil, between November 2021 and May 2022. The animals were restrained with isoflurane, using a mask for induction and maintenance at a rate of 1 to 3% with 100% oxygen. Parameters such as the ventricular and atrial diameter, shortening fraction, and ejection fraction, among others, were measured. Cardiac reference values were assessed. The mild insufficiencies of the mitral and tricuspid valves were the most common findings in cases with alterations. These data serve as a refence for monitoring cardiac health in marmosets, aiding in both conservation and the management of captive primates.